Indigenous Responses to Climate Change: From Climate Colonialism to Indigenous Climate Justice - James Goodman; Heidi Norman; Devleena Ghosh (Cosmopolitan Civil Societies: An Interdisciplinary Journal)
Indigenous peoples have acted across a wide range of fields to address climate change. In all contexts they encounter the barriers of established colonial relations of land and state sovereignty. Indigenous-centred agendas are defined in articulation, with and against these dominant regimes. In this respect they are ‘immanent’, locked into in dialectical struggles for sovereignty. Such contestations are inherently generative: they force new issues onto the agenda, enabling transformation.